Estratégias formativas e impactos no desenvolvimento profissional dos professores - Orvalho, Luísa (2017)
The focus and the object of this qualitative research, carried out under the Post-Doctoral project in Educational Sciences, currently underway at the Faculty of Education and Psychology (FEP), the Portuguese Catholic University, Catholic Porto, entitled “Collaborate to Innovate in Vocational Education “under the supervision of professor José Matias Alves focus on ways, conditions, models of training-action and practical reflective support to the mediation of external consultancy in Advanced Training in Education (FACE) Vocational Education Enhancement axis, Service Support Education Improvement (SAME). The empirical study, based on multiple studies-to-case advice to schools with vocational education, workshop logic training for change, focused on action, aimed at professional development, organizational learning and ongoing collaborative work, supported by transformational leadership, intends to show its impact and transformative effects.